From Prehabilitation to Rehabilitation: A Systematic Review of Resistance Training as a Strategy to Combat Sarcopenia in Pre- and Post-Liver Transplant Patients - Sooraj Vellatt; Jonathan Soldera (Livers)
Background: Sarcopenia, defined as the progressive loss of skeletal muscle mass and strength, is a critical predictor of morbidity and mortality in patients with cirrhosis. In chronic liver disease, sarcopenia exacerbates adverse clinical outcomes and deteriorates quality of life. Physical activity, particularly resistance training, has demonstrated beneficial effects in reversing muscle depletion in various chronic conditions. Aim: This systematic review aimed to evaluate the impact of resistance training on sarcopenia among cirrhotic patients, with a focus on both pre-liver transplant and post-liver transplant populations, to improve clinical outcomes and enhance quality of life. Methods: A systematic review was conducted in accordance with PRISMA 2020 guidelines. PubMed/MEDLINE databases were searched for randomized controlled trials (RCTs) using a standardized search command combining MESH terms and Boolean operators. Studies meeting eligibility criteria and reporting improvements in sarcopenia following resistance training were selected for data extraction. Results: Out of 109 references identified, 12 RCTs were included—10 in pre-transplant and 2 in post-transplant populations. Across studies, resistance training led to measurable improvements in key outcomes: peak VO2 increased by up to 5.3 mL/kg/min, 6 min walk distance improved by 18–97 m, quadriceps muscle thickness increased by up to 1.05 cm, and grip strength gains ranged from 0.4 to 3.8 kg. Postoperative studies reported reductions in fatigue severity scores and length of hospital stay, along with improvements in respiratory pressures and peripheral muscle strength. Conclusions: Resistance training is effective in ameliorating sarcopenia in cirrhotic patients, thereby enhancing pre-transplant status and postoperative quality of life. Clinically, structured exercise programs should be routinely implemented.